Dampak Pemanfaatan Limbah Plastik Menjadi Ecobrick Paving Block Desa Kubu Perahu - Sisdianto, Eris; Lestari , Cahyani; Saputra , Egy Bayu; Aziz , Muhammad Ja'far Abdul; Falevi, Muhammad Reza; Yulianingsih, Rahma; Azzahra, Syalfa Silfina; Ulfah , Ulia; Rosalena , Wanda (Civiliza Publishing, 2024)
This article reports on a community service program conducted by students of UIN Raden Intan Lampung in Kubu Perahu Village, Balik Bukit District, aimed at addressing plastic waste issues through the utilization of ecobrick technology. The program included awareness-raising about the impacts of plastic waste, training in ecobrick paving block production, and the implementation of ecobrick products in village infrastructure development. The results indicate an increased awareness among the community regarding plastic waste management and new skills in ecobrick production. A total of 1,500 ecobrick paving blocks were produced and used to improve footpaths and public areas within the village. This program not only reduced the volume of plastic waste but also enhanced the environmental and infrastructural quality of the village. The success of this program demonstrates that community-based approaches and eco-friendly technologies can effectively address plastic waste issues and provide sustainable benefits to the community